Potato Peels as an Adsorbent for Heavy Metals from Aqueous Solutions: Eco-Structuring of a Green Adsorbent Operating Plackett–Burman Design. (22nd April 2019) - El-Azazy, Marwa; El-Shafie, Ahmed S.; Issa, Ahmed A.; Al-Sulaiti, Maetha; Al-Yafie, Jawaher; Shomar, Basem; Al-Saad, Khalid
Abstract : Treatment of wastewater is becoming a concern of an increasing prominence. Trace amounts of toxic metalloids and heavy metals (HMs) would contaminate large volumes of water. Being present as traces, removal of these ultratrace contaminants from wastewater is challenging. Adsorption of HMs onto raw (RPP) and burnt (BPP) potato peels (PP) is presented in the current treatise. Both adsorbents (RPP and BPP) proved to be efficient in removing Cd(II), Co(II), Cu(II), Fe(II), La(III), Ni(II), and Pb(II) from aqueous solutions. BPP was a more efficient adsorbent compared to RPP. Ecodesign of a model, green adsorbent was structured executing a multivariate approach, design of experiments (DoE). The purpose of using DoE is to maximize the efficiency of BPP (carbonaceous biomass) as a versatile adsorbent. Plackett–Burman design (PBD) was used as a screening phase. Four factors were considered: pH, contact time (CT), heavy metal concentration (HMC), and the adsorbent dose (AD). The Pareto chart of standardized effects shows that the most influential factor is the HMC. These data were confirmed by analysis of variance (ANOVA). Derringer's function was operated to find the best factorial blend that maximizes the adsorption process. The percentage (%) removal of Cd(II), for example, was maximized hitting 100%. Adsorbent surface characterization was performed using FTIR, BET, SEM, TGA/ d TG, and EDX analyses. Adsorption was found to be physisorption that follows Temkin isotherm with sorption energy 66 kJ/mole. Adsorption kinetics was found to be pseudo-first-order. Adsorption capacity ( q m ) for BPP was 239.64 mg/g. The diffusion inside the particles was very limited, while the initial rate of the adsorption was extremely high as shown by the Elovich plot.